Farming Justice on Economic Regulations in Indonesia and France - Said, Zainal; Sih Natalia Sukmi; Rustam Magun Pikahulan; Pradana, Syafa'at Anugrah (Journal of Human Rights, Culture and Legal System, 2025)
This research addresses a significant issue in Indonesia, where 68% of agricultural land is controlled by just 1% of the population, leading to over 3,200 agrarian conflicts in the last decade and impacting approximately 1.8 million farming households. Only 32% of farmers have access to capital, despite being certified landowners, highlighting a stark inequality in land ownership and farmer’s sovereignty compared to modern and institutionalised agricultural system in France. This research explores how France agricultural models can inspire improvements in agrarian governance in Indonesia by analysing the paradigm of agricultural justice through the lens of economic law. This study employs comparative legal methods to examine and differentiate the regulatory frameworks and institutional mechanisms governing land distribution, market control, and peasant protection in both countries. This study finds that, France actively intervenes in its agricultural sector through SAFER, which regulates land transactions, provides CAP, and allocates 50% of SAFER to smallholder farmers, ensuring fair access and preventing corporate dominance. In contrast, 60% of Indonesian agricultural land is controlled by large corporations, with 6 million hectares in dispute. Agrarian reform is hampered by bureaucracy, overlapping regulations, and corruption. KUR programs and fertilizer subsidies often fail to reach intended target. This study recommends adopting the French model to strengthen institutions, transparency, smallholder support, and oversee monopolies.